Nium: Leveraging fintech to disrupt cross-border remittance services - KOH, Annie (Institutional Knowledge at Singapore Management University, 2020)
Set in October 2019, this case presents the remarkable growth journey of Nium, a Singapore-headquartered fintech start-up in digital remittance. The founders are on a mission to disrupt the traditional remittance industry ridden with inefficiency and an opaque pricing structure, and are confident that offering low transaction fees, high transparency and quick transfers would give the incumbent players a run for their money. Since starting out in 2015, Nium had successfully secured US$59.5 million in three rounds of equity funding. By 2019, it was the leading digital remittance operator in Southeast Asia. With a presence in eight markets across North America, Europe and Asia Pacific regions, the value proposition of the fintech start-up was sufficiently compelling to win over investors and customers who had been at the mercy of large financial establishments charging exorbitant fees at unfavourable foreign exchange rates. Looking poised to continue its high growth trajectory, Nium had embarked on a new chapter of market and service expansion. It made inroads into Japan and Indonesia while launching new service platforms that included card-issuing as well as payment collection services for SMEs all over the world. As Nium marks its fifth anniversary of founding, the founders contemplate how the start-up might evolve. Should they pursue an IPO as planned in 2022-23, raise the next round of equity funding, or step into the digital banking arena? Upon completing the case discussion, students would be able to identify the enablers of disruption in the remittance industry, describe various scaling-up strategies used by fintech start-ups and analyse growth options for matured start-ups.